Diagnosis of Neisseria gonorrhoeae Using Molecular Beacon. (31st January 2015) - Sachdev, Divya; Patel, Achchhe Lal; Sonkar, Subash Chandra; Kumari, Indu; Saluja, Daman
Abstract : Neisseria gonorrhoeae is an important sexually transmitted diseases (STD) causing pathogen worldwide. Due to absence of an affordable diagnostic assay, routine screening of gonococcal infection becomes impossible in developing countries where infection rates are maximum. Treatment is given on the basis of symptoms alone which leads to spread of infection. Thus, development of a rapid, sensitive, specific, and PCR based visual diagnostic assay suitable for developing countries, required for better disease management, is aimed at in present study. Endocervical swabs were collected from patients visiting gynecology department of various hospitals in Delhi. In-house PCR based assay was developed and modified to visual assay using molecular beacon for end-point detection. It was evaluated against Roche AMPLICOR NG kit and rmp gene. Specificity of beacon was confirmed by competition experiments. Diagnostic test was 98.21% specific and 99.59% sensitive whereas negative and positive predicted value were 99.40% and 98.78%, respectively. We also observed that twice the concentration (2X) of premix was stable at 4°C for 4 months and dry swab samples gave concordant results with that of wet swabs. These features make the test best suitable for routine diagnosis of genital infections in developing countries.